FROM THEORY TO PRACTICE: ENHANCING ENGLISH LANGUAGE COMPETENCIES IN THE INTEGRATED CLASSROOM - Abdukarimov Abdulvohid, (TADQIQOTLAR, 2026)
This  study  explores  the  transition  from  theoretical  frameworks  of  language learning to practical implementation in the integrated classroom, with a particular focus on enhancing English language competencies. In contemporary language education, the integration of skills, content, and communicative practices has become a central principle, reflecting the need for holistic and learner-centered approaches. The research examines  how  theoretical  models  such  as  communicative  language  teaching,  task-based learning, and content and language integrated learning (CLIL) can be effectively operationalized in classroom settings to develop learners’ linguistic, communicative, and  intercultural  competencies.  By  applying  pedagogical  analysis,  comparative evaluation, and classroom-oriented perspectives, the study identifies key strategies for bridging the gap between theory and practice. The findings suggest that integrated instruction  not  only  improves  language  proficiency  across  the  four  skills  listening, speaking, reading, and writing but also enhances critical thinking, collaboration, and learner  autonomy.  The  paper  highlights  the  importance  of  adaptive  teaching methodologies,  contextualized  learning  environments,  and  reflective  practice  in achieving effective language education outcomes.